Exposure of Free-Ranging Wild Carnivores and Domestic Dogs to Canine Distemper Virus and Parvovirus in the Cerrado of Central Brazil - Furtado, Mariana Malzoni; Kida Hayashi, Erika Midori; Allendorf, Susan Dora [UNESP]; Coelho, Claudio Jose; Almeida Jacomo, Anah Tereza de; Megid, Jane [UNESP]; Ramos Filho, Jose Domingues; Silveira, Leandro; Torres, Natalia Mundim; Ferreira Neto, Jose Soares (Springer, 2016)
Human population growth around protected areas increases the contact between wild and domestic animals, promoting disease transmission between them. This study investigates the exposure of free-ranging wild carnivores and domestic dogs to canine distemper virus (CDV) and parvovirus in Emas National Park (ENP) in the Cerrado savanna of central Brazil. Serum samples were collected from 169 wild carnivores, including the maned wolf (Chrysocyon brachyurus), crab-eating fox (Cerdocyon thous), hoary fox (Pseudalopex vetulus), puma (Puma concolor), olo), jaguarundi (Herpailurus yagouaroundi), striped hog-nosed skunk (Conepatus semistriatus) and coati (Nasua nasua), and from 35 domestic dogs living ocelot (Leopardus pardalis), pampas cat (Leopardus colocon rural properties bordering ENP. Serological tests showed that 10.6% of wild carnivores (maned wolves, crab-eating foxes and ocelots) and 71.4% of domestic dogs were exposed to CDV, and 56.8% of wild carnivores, including all species sampled except coatis, and 57.1% of domestic dogs were exposed to parvovirus. This report is the first to indicate that the free-ranging pampas cat, jaguarundi and striped hog-nosed skunk are exposed to parvovirus. CDV and parvovirus deserve attention in ENP, and it is extremely important to monitor the health of carnivore populations and perform molecular diagnosis of the viruses to determine the possible involvement of the domestic dog in their transmission.
Keywords: crab-eating fox; conservation Medicine; infectious disease; maned wolf; serosurvey; virus; wild canids; wild felids